EFEKTIVITAS MODEL PEMBELAJARAN INKUIRI ILMIAH BERBASIS KEARIFAN LOKAL BUDAYA DAYAK KETAPANG TERHADAP MINAT BELAJAR MAHASISWA: STUDI LITERATUR MAHASISWA POLITEKNIK NEGERI KETAPANG - Putrini R Harahap, Saima (Universitas Islam Negeri Sumatera Utara Medan, 2023)
This study explores the effectiveness of the Scientific Inquiry Learning Model Based on Local Wisdom of Dayak Ketapang Culture on students' learning interest, with a focus on existing related literature. Through a review of previously published articles, the study findings highlight that the integration of Ketapang Dayak cultural local wisdom in scientific learning can significantly increase students' interest in learning. Research also emphasizes the importance of a contextual approach in introducing scientific concepts to students, allowing them to feel the relevance of the subject matter to their lived realities. The results of the analysis show that the integration of local wisdom in scientific learning has great potential to strengthen students' interest in learning and improve their academic achievement. The implications of this research reinforce the importance of promoting and actively supporting the integration of local wisdom in education to create an inclusive and effective learning environment